2017
DOI: 10.1177/1087054717718263
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram Theta/Beta Ratio and Spectral Power Correlates of Executive Functions in Children and Adolescents With AD/HD

Abstract: The results do not support the diagnostic value of TBR. Instead, given the heterogeneous features, the results support the prognostic value of EEG in AD/HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 60 publications
(120 reference statements)
0
19
0
Order By: Relevance
“…TBR might be a biomarker for prefrontal lobe mediated executive control or attentional control functions 4 or might be an inhibitory biomarker. 7 Zhang et al 24 explored the association with resting EEG and neuropsychological tasks and supported the neurophysiological states as biomarkers for neuropsychological functions. In one study of 220 6- to 12-year-old children 25 (54 in ADHD inattention subtypes [ADHD-I], 53 in ADHD hyperactivity/impulsivity subtypes [ADHD-H/I], 57 in ADHD combined subtype [ADHD-C], and 56 in typical development) did a test of variables of attention (TOVA) and concurrent EEGs (at CZ and FP1) which showed that ADHD-I had a higher TBR than ADHD-C did at CZ, but a lower TBR at FP1.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…TBR might be a biomarker for prefrontal lobe mediated executive control or attentional control functions 4 or might be an inhibitory biomarker. 7 Zhang et al 24 explored the association with resting EEG and neuropsychological tasks and supported the neurophysiological states as biomarkers for neuropsychological functions. In one study of 220 6- to 12-year-old children 25 (54 in ADHD inattention subtypes [ADHD-I], 53 in ADHD hyperactivity/impulsivity subtypes [ADHD-H/I], 57 in ADHD combined subtype [ADHD-C], and 56 in typical development) did a test of variables of attention (TOVA) and concurrent EEGs (at CZ and FP1) which showed that ADHD-I had a higher TBR than ADHD-C did at CZ, but a lower TBR at FP1.…”
Section: Introductionmentioning
confidence: 98%
“…13,14 On the other hand, 3 levels of endophenotypes in ADHD have been proposed, 15 and the associations between behavioral symptoms, neuropsychological functions, neurophysiological technique, and neuropsychological mechanisms have become more critical in ADHD studies. [16][17][18][19][20][21][22] Associations between EEGs are also important for ADHD research 12,23,24 but it is unclear what specific processes are associated with TBR. TBR might be a biomarker for prefrontal lobe mediated executive control or attentional control functions 4 or might be an inhibitory biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…While non-REM (NREM) sleep did not differ significantly in ADHD compared to normal controls, REM sleep was of longer duration and there was an increase in the number of sleep cycles 42-44. It was suggested, that increased number of sleep cycles may impose faster transition to REM sleep explaining in part the longer duration of REM sleep in ADHD 44 .The main relevant alterations in PSG microstructure in ADHD children are increased theta activity mainly during REM sleep 45 . Similar findings of increased thetabeta ratio in awake surface EEG in ADHD was associated with impaired inhibitory control 46 . The consistently demonstrated altered theta activity both during waking state and sleep led Scarpelli to conclude that increased theta activity may be a biological marker of ADHD in children in spite of the fact that it was based on only 8 studies published between the years 2006-2017 43 .…”
Section: Sleep Problems In Youngsters With Adhdmentioning
confidence: 52%
“…Several EEG waking studies showed that the theta activity has a pivotal role in ADHD functioning [52]. In particular, children with ADHD show an increased absolute theta power, often associated with a decreased beta power.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, children with ADHD show an increased absolute theta power, often associated with a decreased beta power. This leads to an increased theta/beta ratio, recognized as a neurophysiological marker for helping to diagnose ADHD [52]. These findings could be conceptualized in terms of “cortical hypoarousal” and of unstable vigilance regulation [53].…”
Section: Discussionmentioning
confidence: 99%